Assessment Of Bornean Orangutans Based On Nest Structure Using Unmanned Aerial Vehicle (UAV), Nesting Site Preferences And Parasitic Prevalence - Kamaruszaman, Salniza Akmar (2019)
In the current developing era, the importance of orangutans is being forgotten. The function of rehabilitation centres in conserving the animals need to be monitored and supported. Orangutans nesting skill and parasitic prevalence illustrate an important role in a rehabilitation centre. Hence, this study aims to determine the variation of nest structure quantitatively, the nesting site preference and the prevalence of gastrointestinal parasite in orangutans.